Brain pericyte biology: from physiopathological mechanisms to potential therapeutic applications in ischemic stroke - Fu, Jiaqi; Liang, Huazheng; Yuan, Ping; Wei, Zhenyu; Zhong, Ping (Frontiers in Cellular Neuroscience, 2023)
Pericytes play an indispensable role in various organs and biological processes, such as promoting angiogenesis, regulating microvascular blood flow, and participating in immune responses. Therefore, in this review, we will first introduce the discovery and development of pericytes, identification methods and functional characteristics. Then focus on brain pericytes, on the one hand, to summarize the functions of brain pericytes under physiological conditions, mainly discussing from the aspects of stem cell characteristics, contractile characteristics and paracrine characteristics; on the other hand, to summarize the role of brain pericytes under pathological conditions, mainly taking ischemic stroke as an example. Finally, we will discuss and analyze the application and development of pericytes as therapeutic targets, providing the research basis and direction for future microvascular diseases, especially ischemic stroke treatment.